Design fora de série: percursos da produção contemporânea em São Paulo: Estudio Manus e ,ovo - BARBOSA, Valéria Cilene (2018)
This dissertation analyzes the design of products under the authorial bias, dissociated from the industry, in the area where it favors playful and semantic aspects. To this dimension of design we call it out of series. As a contemporary alternative of acting in product design, in the out-of-series design, self-production predominates, carried out by means of artisan or low tech processes, or even high tech. In these processes, creation does not take place in response to an external demand, seeking to solve a problem, but derives from an idea, interest, proposition or enchantment on the part of the designer. The circulation and insertion of this type of product was initially thanks to curating in galleries and shows, as well as design awards, demonstrating its hybridization with the artistic universe. Production often occurs in limited editions or single pieces, or even on a small scale. The main cases of analysis were the Studio Manus, by Caio Medeiros and Daniela Scorza, and the double, egg, by Gerson de Oliveira and Luciana Martins, both for having a relevant trajectory in the national design panorama. Understanding how the processes of creation, production and insertion of these objects in the Brazilian context are the objective of this study. It is also important to understand the paradigm changes that occur in the contemporary production of product design in Brazil, especially in São Paulo, and how the production of the first professionals allowed a new generation of product designers to have a space of performance and circulation.